Constructing the impact of industry 4.0 on SMEs performance among Malaysian manufacturing organisation - Bali Mahomed, Anuar Shah; Sheikh Mokhtar, Siti Salwa; Ibrahim, Saadiatul; Mohsin Ali, Rana; Amin, Dawood (Science Alert, 2019)
The level of Industry 4.0 usage among Malaysian organizations have yet to reach its optimum level, particularly among SMEs, which are lagging behind SMEs in the developed countries. This paper explores the factor impacted the adoption of Industry 4.0 and proposed a conceptual framework which incorporates cultural and technological factors contributing to Industry 4.0 adoption and SMEs performance among Malaysian manufacturing organization.